2020
DOI: 10.12968/bjon.2020.29.20.1206
|View full text |Cite
|
Sign up to set email alerts
|

A service evaluation: impact of nurse-led regional familial hypercholesterolaemia service on a hospital adult lipid clinic

Abstract: The authors evaluated the impact of genetic screening for familial hypercholesterolaemia (FH) in a lipid clinic cohort of patients with definite and possible FH as defined by the Simon Broome Register (SBR) criteria. Methods: Patients with a lipid clinic diagnosis of definite and possible FH based on the SBR criteria were referred to a nurse-led regional service for FH genetic testing. Findings: 140 patients were referred for genetic testing. Six had SBR-definite FH due to the presence of tendon xanthomata and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…One clinic found high levels of uptake in genetic counseling and subsequent testing for FH (25% with a genetic risk result for FH (6/24)), and intensification of lipid-lowering therapy that resulted in a 79 mg/dl reduction in average LDL-C ( n = 12, P < 0.001) and 75% (9/12) achieving LDL-C target goals [35 ▪▪ ]. Another lipid clinic study utilized the SB Criteria to identify individuals with definite and possible FH and found that 100% of patients with definite FH and 25% (34/134) of those with possible FH had a genetic risk variant [36].…”
Section: Resultsmentioning
confidence: 99%
“…One clinic found high levels of uptake in genetic counseling and subsequent testing for FH (25% with a genetic risk result for FH (6/24)), and intensification of lipid-lowering therapy that resulted in a 79 mg/dl reduction in average LDL-C ( n = 12, P < 0.001) and 75% (9/12) achieving LDL-C target goals [35 ▪▪ ]. Another lipid clinic study utilized the SB Criteria to identify individuals with definite and possible FH and found that 100% of patients with definite FH and 25% (34/134) of those with possible FH had a genetic risk variant [36].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the familial hypercholesterolaemia (FH) service, patients are referred for specialized nurse assessment for FH risk, with possible genetic testing. If confirmed to have a FH-associated gene, patients are given lifestyle counseling from nurses and further follow-up and treatment as indicated ( Wilkinson et al, 2020 ). Documents such as these can provide some direction for other countries as they develop the infrastructure to integrate GG into nursing practice.…”
Section: Background and Purposementioning
confidence: 99%
“…For example, reflex tumour testing (also referred to as somatic testing) for critical genetic aberrations is now observed across different types of cancer, including microsatellite instability testing in colorectal and endometrial cancers, which subsequently guides treatment decisions. The collection of a three-generation family health history remains an effective way to identify genetic risk and an opportunity to provide health education for screening and lifestyle education associated with hypercholesterolaemia (Wilkinson et al 2020). As such, it is imperative that nurses have the requisite knowledge and skills to provide genomics-informed care and to understand how genomics knowledge is linked to existing nursing knowledge and practices (Flowers et al 2020).…”
Section: Introductionmentioning
confidence: 99%